EVALUATION OF THE POLLUTANT LEVEL OF OCHRATOXIN A (OTA) THROUGH IMMUNOAFFINITY COLUMNS AND HIGH EFFICIENCY LIQUID CHROMATOGRAPHY IN Coffea arabica L. "COFFEE" - Milla Flores, Félix Hugo (2020)
The study aims to evaluate the contaminant level of Ochratoxin A (OTA) in Coffea arabica L. "coffee", roasted, purified by immunoaffinity columns and quantified by High Efficiency Liquid Chromatography (HPLC). OTA is a nephrotoxic-carcinogenic mycotoxin capable of causing adverse effects on human and animal health. It is found in many processed and unprocessed foods, including coffee, which is a food with high consumption. Roasted coffee samples were collected in the coffee zone of Chanchamayo, department of Junin-Peru. The separation and purification of the Ochratoxin A was performed by NeoColumn immunoaffinity columns, subsequently quantification was performed by HPLC with fluorescence detector, at an excitation wavelength of 333 nm and emission wavelength of 460 nm. Finally, the test of percent of recovery were carried out at the contaminant level of 5 ppb. The results obtained in roasted coffee samples have a content of 0,216 and 0,444 ppb of OTA which do not exceed the limits allowed by international law. The recovery rate at level 5 ppb was 76,231 %. The study highlights the importance of traceability in a product of frequent consumption at national and international level, in order to ensure its safety.